Defect study of phosphorous doped a-Si:H thin films using cathodoluminescence, IR and Raman spectroscopy - Singh C.B.; Bhattacharya S.; Patel U.S.; Singh V.; Bhargav P.B.; Ahmed N. (My University, 2025)
The phosphorous (P) doping induced defects and deviation in microstructural properties of a-Si:H films have been investigated by Infrared (IR), Raman and Cathodoluminescence (CL) spectroscopy. The analysis of local vibration mode of IR and Raman spectra points out the evolution of defects and cluster structure with a P-doping in a-Si:H films. Undoped a-Si: H films show no CL spectra while it emerges in P-doped films. Intensification in CL spectra with P-doping intimates that the crystallites and defects in films are the origin of CL spectra. CL peaks are emanated from intrinsic structural defects, interstitial cations and two-fold coordinated silicon in films. Peaks at 784 nm and 945 nm in CL spectra are originated from Si micro-crystals. © 2023 Elsevier B.V.